Satellite-surface perspectives of air quality and aerosol-cloud effects on the environment: An overview of 7-SEAS/BASELInE - Si Chee Tsay (2018)
© Taiwan Association for Aerosol Research. The objectives of 7-SEAS/BASELInE (Seven SouthEast Asian Studies/Biomass-burning Aerosols & Stratocumulus Environment: Lifecycles & Interactions Experiment) campaigns in spring 2013–2015 were to synergize measurements from uniquely distributed ground-based networks (e.g., AERONET, MPLNET) and sophisticated platforms (e.g., SMARTLabs, regional contributing instruments), along with satellite observations/retrievals and regional atmospheric transport/chemical models to establish a critically needed database, and to advance our understanding of biomass-burning aerosols and trace gases in Southeast Asia (SEA). We present a satellite-surface perspective of 7-SEAS/BASELInE and highlight scientific findings concerning: (1) regional meteorology of moisture fields conducive to the production and maintenance of low-level stratiform clouds over land, (2) atmospheric composition in a biomass-burning environment, particularly tracers/markers to serve as important indicators for assessing the state and evolution of atmospheric constituents, (3) applications of remote sensing to air quality and impact on radiative energetics, examining the effect of diurnal variability of boundary-layer height on aerosol loading, (4) aerosol hygroscopicity and ground-based cloud radar measurements in aerosol-cloud processes by advanced cloud ensemble models, and (5) implications of air quality, in terms of toxicity of nanoparticles and trace gases, to human health. This volume is the third 7-SEAS special issue (after Atmospheric Research, vol. 122, 2013; and Atmospheric Environment, vol. 78, 2013) and includes 27 papers published, with emphasis on air quality and aerosol-cloud effects on the environment. BASELInE observations of stratiform clouds over SEA are unique, such clouds are embedded in a heavy aerosol-laden environment and feature characteristically greater stability over land than over ocean, with minimal radar surface clutter at a high vertical spatial resolution. To facilitate an improved understanding of regional aerosol-cloud effects, we envision that future BASELInE-like measurement/modeling needs fall into two categories: (1) efficient yet critical in-situ profiling of the boundary layer for validating remote-sensing/retrievals and for initializing regional transport/chemical and cloud ensemble models, and (2) fully utilizing the high observing frequencies of geostationary satellites for resolving the diurnal cycle of the boundarylayer height as it affects the loading of biomass-burning aerosols, air quality and radiative energetics.